2018
DOI: 10.1111/bjso.12304
|View full text |Cite
|
Sign up to set email alerts
|

Meeting a nice asylum seeker: Intergroup contact changes stereotype content perceptions and associated emotional prejudices, and encourages solidarity‐based collective action intentions

Abstract: Intergroup contact can improve majority members' perception of minorities. Integrating the intergroup contact hypothesis with the stereotype content model and BIAS-Map, we hypothesized that positive intergroup contact improves German majority members' evaluations of asylum seekers on the warmth and competence dimensions. Using crosssectional survey data and structural equation modelling, we found support for this hypothesis (Study 1a, N = 182). Warmth and competence perceptions, in turn, predicted specific int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 49 publications
3
62
1
Order By: Relevance
“…In the personal view condition, the instruction read: 'Responding to the questions we are interested in your personal opinion how you would rate various social groups'. 1 Thereafter, we asked participants on a scale from 1 = not at all to 5 = completely how warm, friendly, and well-intentioned for warmth, and competent, independent, and competitive for competence 2 (Asbrock, 2010;Eckes, 2002;Kotzur et al, 2017;Kotzur, Friehs, et al, 2019;Kotzur, Sch€ afer, & Wagner, 2019) either society (society's perspective condition) or themselves (personal perspective condition) rated six social groups from different quadrants in the SCM space (Asbrock, 2010): athletes and students (high warmth/high competence), elderly (high warmth/low competence), Muslims (midwarmth/mid-competence), the rich (low warmth/high competence), and the homeless (low warmth/low competence). 3 After providing demographical data, participants were thanked and had the opportunity to get compensated for their participation with partial course credit.…”
Section: Studymentioning
confidence: 99%
“…In the personal view condition, the instruction read: 'Responding to the questions we are interested in your personal opinion how you would rate various social groups'. 1 Thereafter, we asked participants on a scale from 1 = not at all to 5 = completely how warm, friendly, and well-intentioned for warmth, and competent, independent, and competitive for competence 2 (Asbrock, 2010;Eckes, 2002;Kotzur et al, 2017;Kotzur, Friehs, et al, 2019;Kotzur, Sch€ afer, & Wagner, 2019) either society (society's perspective condition) or themselves (personal perspective condition) rated six social groups from different quadrants in the SCM space (Asbrock, 2010): athletes and students (high warmth/high competence), elderly (high warmth/low competence), Muslims (midwarmth/mid-competence), the rich (low warmth/high competence), and the homeless (low warmth/low competence). 3 After providing demographical data, participants were thanked and had the opportunity to get compensated for their participation with partial course credit.…”
Section: Studymentioning
confidence: 99%
“…Indeed, studies from North America, Europe, and beyond indicate that receiving society members’ contact with immigrants can yield positive attitudes toward immigrant populations (Binder et al., ; Ellison, Shin, & Leal, ; Fetzer, ). For instance, in one lab‐based experiment conducted in Germany, participants were asked to engage in a structured conversation with either “Abdelrahim,” a confederate who supposedly immigrated to Germany as a refugee, or “Frank,” a confederate who supposedly did not have a migration background (Kotzur, Schäfer, & Wagner, ). After an evaluation of the conversation that appeared to mark the end of the study, participants were invited to participate in a second, and ostensibly unrelated, study in which they were asked to provide their evaluations of refugees in general, among other things.…”
Section: Contact As a Facilitator Of Positive Intergroup Relationsmentioning
confidence: 99%
“…Moreover, parallel surveys of first‐generation Mexican and Indian immigrants indicated that the more contact they had with White and Black Americans, the more they felt welcomed by these groups; both the effects of contact on welcoming and feeling welcomed were enhanced to the extent that respondents rated their contact as friendly in nature. Relatedly, studies indicate that positive intergroup contact can lead receiving society members to show less opposition to supportive immigration policies (McLaren, ) and even to participate in protests to promote the interests of immigrant outgroups (Kotzur, Schäfer, et al., ).…”
Section: Contact As a Facilitator Of Positive Intergroup Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern Italy, therefore, is one of the chief destinations for this international migration. Although each country that accepts asylum seekers tries to offer social support for the newcomers, asylum seekers continue to face widespread rejection as demonstrated by the number of hate crimes committed against them, often with the support of nationalist movements and parties (Kotzur et al 2019).…”
Section: Introductionmentioning
confidence: 99%